Maintaining Radiology Quality with National Hospital Accreditation Standards - Mahmudah, Dian; Hasmy, Achmad; Hariri, Ahmad; Wahyuni, Wilda (International Journal of Natural and Health Sciences, 2024)
Radiology quality assurance is an important method to ensure the quality of radiology services provided by hospitals. One of the processes used to assess and review quality assurance systems in hospitals, including radiology services, is hospital accreditation. This article intends to explore radiology quality assurance activities during the hospital accreditation process in Indonesia. In this article, a literature study is used to gather data from several highly reputable sources from scientific journals, accreditation standards, and government publications. Research findings show that hospital accreditation is critical for radiology quality assurance. Hospitals that follow accreditation procedures must meet certain standards applied by the Ministry of Health. This process ensures that the hospital adheres to best practices in surgery and radiology services and that the quality of these services is maintained regularly. Hospital accreditation is a successful technique in radiological quality assurance efforts. Hospitals can improve radiology service standards and provide higher quality assurance for patients and the public by following certification procedures. It is thought that this research will help hospitals and other stakeholders, including professional organizations determine a more effective radiology quality assurance system in the future